Relationship between speed changes in the 100-m sprint and maximum speed in the 300-m maximum speed test among japanese elite wheelchair racers - Kawabata, K.; Nishimura, Y.; Ibusuki, T.; Mitsui, T.; Kamijo, Y.-i.; Umemoto, Y.; Tajima, F. (International Journal of Sport & Health Science, 2022)
This study aimed to clarify the relationship between maximum speed and change in speed during 100-m sprints among elite Japanese wheelchair racers (T54 class). The study participants were instructed to sprint at maximum effort for the last 50-m section of a 300-m distance and from the starting line to a distance of 100 m. Propulsive movements were captured at 240 Hz using a high-speed camera. The mean (±standard deviation) maximum speed (MxSP) obtained in the 300-m sprint was 9.03±0.19 m/s. The peak speed of the 100-m sprint (PkSP) was 8.42±0.33 m/s and the speed during the 100-m sprint relative to the maximum speed (%MxSP) was 93.2%±2.6%. The PkSP appeared in the final section for all but one wheelchair racer, for whom it appeared in the 90-95- and 95-100-m sections. No wheelchair racers were able to achieve the MxSP within 100 m. However, as the MxSP correlated with speed after the last 30 m, it is possible that times in the second half of the 100-m sprint could be improved by increasing the MxSP. The %MxSP in the final section correlated with the 100-m time, and wheelchair racers with a higher %MxSP in the final section showed higher speeds from the first half of the race.